The Description of Stress Levels among Medical Students - Della Rovita Ndoen; Dian Lestari Anakaka; Diana Aipipidely (Journal of Health and Behavioral Science, 2021)
Abstract. Stress is the body’s reaction to any change that requires an adjustment or response. The body reacts to these changes with physical, mental, and emotional responses. This research aims to comprehend the stress levels of students in the medical faculty of Nusa Cendana University, Kupang based on sex and years. The design in this research is descriptive quantitative by collecting data used stress scale (consisted of 40 items) compiled by the researcher. The trial results of the measuring instruments shows that the value of Cronbach’s Alpha is 0.936. The participants are 173 students. The result shows that medical students have a moderate stress level that seen from the percentage is 85.5%, and female students have a higher stress level than male based on sex, then last year students have a higher stress level than the other students based on year. Abstrak. Stres adalah reaksi tubuh terhadap setiap perubahan yang membutuhkan penyesuaian atau respons. Tubuh bereaksi terhadap perubahan ini dengan tanggapan fisik, mental, dan emosional. Penelitian ini bertujuan untuk mengetahui tingkat stres mahasiswa Fakultas Kedokteran Universitas Nusa Cendana Kupang berdasarkan jenis kelamin dan umur. Desain dalam penelitian ini adalah deskriptif kuantitatif dengan pengumpulan data menggunakan skala stres (terdiri dari 40 item) yang disusun oleh peneliti. Hasil uji coba alat ukur menunjukkan bahwa nilai Cronbach's Alpha adalah 0,936. Pesertanya 173 siswa. Hasil penelitian menunjukkan bahwa mahasiswa kedokteran memiliki tingkat stres yang sedang dilihat dari persentase 85,5%, dan mahasiswa perempuan memiliki tingkat stres yang lebih tinggi dibandingkan laki-laki berdasarkan jenis kelamin, maka tahun lalu mahasiswa memiliki tingkat stres yang lebih tinggi dibandingkan mahasiswa lain berdasarkan tahun.